2020
DOI: 10.3390/cells9030770
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Reference Genes for Gene Expression Studies by RT-qPCR in HepaRG Cells during Toxicity Testing and Disease Modelling

Abstract: Gene expression analysis by quantitative real-time polymerase chain reaction (RT-qPCR) is routinely used in biomedical studies. The reproducibility and reliability of the data fundamentally depends on experimental design and data interpretation. Despite the wide application of this assay, there is significant variation in the validation process of gene expression data from research laboratories. Since the validity of results depends on appropriate normalisation, it is crucial to select appropriate reference ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…Murine and human genespecific primers were as follows: rat Ercc2: 5 -ATGGGCTGCTGGTCTACTTC-3 (F), 5 -TCCAGTGGATAAGCCCGTTG-3 (R); rat Glyceraldehyde-3-phosphate dehydrogenase (Gapdh): 5 -ATGGGAGTTGCTGTTGAAGTC-3 (F), 5 -CCGAGGGCCCACTAAAGG-3 (R); human ERCC2: 5 -CCTACATGCGGGAGCTCAAA-3 (F), 5 -CAGCGGATATGCTCTCTGGT-3 (R); human GAPDH: 5 -GACAGTCAGCCGCATCTTCT-3 (F), 5 -GCGCCCAATACGACCAAA-TC-3 (R). As reference genes used for the normalization of RT-qPCR data can sometimes vary under different experimental conditions [34], we verified that Ct values of human GAPDH and murine Gapdh expression were stable in our experiments.…”
Section: Rna Analysessupporting
confidence: 71%
“…Murine and human genespecific primers were as follows: rat Ercc2: 5 -ATGGGCTGCTGGTCTACTTC-3 (F), 5 -TCCAGTGGATAAGCCCGTTG-3 (R); rat Glyceraldehyde-3-phosphate dehydrogenase (Gapdh): 5 -ATGGGAGTTGCTGTTGAAGTC-3 (F), 5 -CCGAGGGCCCACTAAAGG-3 (R); human ERCC2: 5 -CCTACATGCGGGAGCTCAAA-3 (F), 5 -CAGCGGATATGCTCTCTGGT-3 (R); human GAPDH: 5 -GACAGTCAGCCGCATCTTCT-3 (F), 5 -GCGCCCAATACGACCAAA-TC-3 (R). As reference genes used for the normalization of RT-qPCR data can sometimes vary under different experimental conditions [34], we verified that Ct values of human GAPDH and murine Gapdh expression were stable in our experiments.…”
Section: Rna Analysessupporting
confidence: 71%
“…Many studies have shown that there is no single reference gene that could be effectively used in the RT-qPCR in all species or under all experimental conditions ( Suzuki et al, 2000 ; Zhou et al, 2018 ). For example, Brzeszczyńska et al (2020) proved that the classical reference gene in HepaRG cells such as GAPDH was altered by drug treatment. Vorachek et al (2013) found that the commonly used reference genes, PGK1 , ACTB , and B2M for neutrophils were not reliable reference genes under different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Data generated within this study are included in the manuscript and Supplementary Materials . Studies obtained through the systematic review of published literature and analyzed within this study are quoted in the References section [ 16 , 22 , 45 , 47 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ,…”
mentioning
confidence: 99%